The application of optical packet switching in future communicationnetworks. - O'Mahony, M.J (IEEE Communications magazine)
Telecommunication networks are experiencing a dramatic increase in demand for capacity, much of it related to the exponential takeup of the Internet and associated services. To support this demand economically, transport networks are evolving to provide a reconfigurable optical layer which, with optical cross-connects, will realize a high-bandwidth flexible core. As well as providing large capacity, this new layer will be required to support new services such as rapid provisioning of an end-to-end connection under customer control. The first phase of network evolution, therefore, will provide a circuit-switched optical layer characterized by high capacity and fast circuit provisioning. In the longer term, it is currently envisaged that the bandwidth efficiency associated with optical packet switching (a transport technology that matches the bursty nature of multimedia traffic) will be required to ensure economic use of network resources. This article considers possible network application scenarios for optical packet switching. In particular, it focuses on the concept of an optical packet router as an edge network device, functioning as an interface between the electronic and optical domains. In this application it can provide a scalable and efficient IP traffic aggregator that may provide greater flexibility and efficiency than an electronic terabit router with reduced cost. The discussion considers the main technical issues relating to the concept and its implementation